1981
DOI: 10.1111/j.1365-2273.1981.tb01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin in acute otitis media: a double-blind placebo-controlled trial

Abstract: The effect of peroral penicillin-V (55 mg/kg/day in 7 days) on acute otitis media was studied in 149 children between the ages of 1 and 10 years in a double-blind, placebo-controlled investigation. The parameters of the disease employed were symptom scores for earache, fever and common cold, the use of analgetics, otoscopy, as well as tympanometry. The children were followed-up for 3 months. Penicillin had no effect on fever and common cold, but earache was significantly reduced on the 2nd day of treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 14 publications
2
58
1
Order By: Relevance
“…However, one of these trials included all randomised patients in the primary analysis at day four (Damoiseaux 2000). In two of the 13 trials the total number of loss to follow-up/exclusions are described but it was unclear from which treatment group children were excluded (Halsted 1968;Mygind 1981). For the review of immediate antibiotics against expectant observation, the loss to follow-up was below 5% in two of the five trials ( …”
Section: Incomplete Outcome Datamentioning
confidence: 99%
See 2 more Smart Citations
“…However, one of these trials included all randomised patients in the primary analysis at day four (Damoiseaux 2000). In two of the 13 trials the total number of loss to follow-up/exclusions are described but it was unclear from which treatment group children were excluded (Halsted 1968;Mygind 1981). For the review of immediate antibiotics against expectant observation, the loss to follow-up was below 5% in two of the five trials ( …”
Section: Incomplete Outcome Datamentioning
confidence: 99%
“…Two trials compared penicillin for seven days with placebo (Mygind 1981;Thalin 1985), four trials compared amoxicillin for seven to 14 days with or without myringotomy with placebo (Burke 1991;Damoiseaux 2000;Kaleida 1991;Le Saux 2005), and four trials compared amoxicillin/clavulanate for seven to 10 days with placebo (Appelman 1991;Hoberman 2011;Tähtinen 2011;Tapiainen 2014 …”
Section: Interventions and Comparatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve trials were double-blind, placebo-controlled, parallelgroup randomised clinical trials (Appelman 1991;Burke 1991;Damoiseaux 2000;Halsted 1968;Hoberman 2011;Howie 1972;Kaleida 1991;Le Saux 2005;Mygind 1981;Tähtinen 2011;Tapiainen 2014;Thalin 1985), while one trial had a 2 x 2 factorial design (van Buchem 1981a andvan Buchem 1981b).…”
Section: Designmentioning
confidence: 99%
“…Antimicrobial therapy is one of the cornerstones in the management of AOM but some studies have suggested that its routine use is not indicated (17)(18)(19). As the most cases of AOM resolve spontaneously (20), antimicrobial therapy is not always necessary.…”
Section: Treatmentmentioning
confidence: 99%